Mental Health Assessment in Professors’ Training in Two Chilean Universities - Ossa, Carlos J. (2015)
This study analyzed the evaluation of professors of pedagogy and directors programs, about the importance of mental health in vocational training, and factors that might influence this valuation. The methodology includes participation of 17 academicians (professors and belonging to the managerial staff) of two universities in southern Chile. A survey with closed and open questions, and in-depth interviews were used to collect information. Data was analyzed using content analysis. The results show that teachers have, mostly, a high personal assessment of the topic ( = 2.8, between 0 and 3). There is, on the other hand, an ambivalent valuation on the part of the institutions; a lack of knowledge and a low conceptual and procedural proficiency of pedagogues, and a low priority as a competence in their training (59% of participants are not aware of the existence of any programs or courses related to this subject). The ambivalence in institutions, its importance as competence in teachers’ training and the consistency with the low priority given to the subject in public policies are discussed.